Chalcolithic and Bronze Age pottery from the field survey in northwestern Cyprus, 1992-1999 - Maliszewski, Dariusz (Oxford: Archaeopress, 2013)
"The material presented here is derived from an extensive survey conducted by the Polis-Pyrgos Archaeological Project (PAP) in 1992-1994, 1996-1997, and 1999 in the area between the western bank of the Chrysochou River and Kato Pyrgos in northwestern Cyprus. This is the first comprehensive publication of ceramics and ground stone artefacts from the neighbouring area of Polis tis Chrysochous (Polis), formerly ancient Marion and Arsinoe. The pottery constitutes the bulk of the material. Because of the number of artefacts the material will be presented in two volumes. The main task of each contribution is to present the artefacts recorded in its local, regional and whole island context, as far as possible. The second volume will contain post-prehistoric ceramics, Chalcolithic to Iron Age ground stone artefacts, as well as contribution on the environment and resources."--Publisher's website. The material presented here is derived from an extensive survey conducted by the Polis-Pyrgos Archaeological Project (PAP) in 1992 1994, 1996 1997, and 1999 in the area between the western bank of the Chrysochou River and Kato Pyrgos in northwestern Cyprus. This is the first comprehensive publication of ceramics and ground stone artefacts from the neighbouring area of Polis tis Chrysochous (Polis), formerly ancient Marion and Arsinoe. The pottery constitutes the bulk of the material. Because of the number of artefacts the material will be presented in two volumes. The main task of each contribution is to present the artefacts recorded in its local, regional and whole island context, as far as possible. The second volume will contain post-prehistoric ceramics, Chalcolithic to Iron Age ground stone artefacts, as well as contribution on the environment and resources. On the basis of the data examined, and despite several limitations, it has been possible to identify ten Chalcolithic and twenty-nine Bronze Age sites, and thus to generate the first picture of prehistoric occupation in northwestern Cyprus, which should no longer be perceived as terra inhabitata in that time."
Data and survey method -- Chalcolithic. Early chalcolithic-middle chalcolithic ; Early chalcolithic-late chalcolithic ; Middle chalcolithic-late chalcolithic ; Late chalcolithic. -- Bronze age. Early Cypriot-middle Cypriot ; Early Cypriot-late Cypriot ; Late Cypriot ; Bronze age?. -- Prehistoric occupation in light of the survey pottery. Chronological and spatial distribution ; Concluding remarks, problems, and prospects.
Includes bibliographical references (79-85).
Keywords: Pottery, Prehistoric -- Cyprus; Bronze age -- Cyprus; Copper age -- Cyprus; Cyprus -- antiquities; Cyprus -- antiquites -- Polis-Ryrgos